2005
DOI: 10.2135/cropsci2004.0137
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Model for Pollen‐Mediated Gene Flow in Wheat

Abstract: seed. Gene flow can enhance the genetic diversity of plant populations and may therefore increase the popu-The extent of pollen-mediated gene flow (PMGF) in wheat (Tritilation's ability to respond to changing stressors in the cum spp. L.) as a function of distance from a pollinator source has been measured in recent field studies. Wheat is primarily self-pollinated; environment. In plants, pollen dispersal is the primary however, some cross-pollination can occur depending on biological, mode of gene flow among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 60 publications
8
69
1
Order By: Relevance
“…Pollen-mediated gene flow has been quantified in detail in several crops using transgenic and marker genes including wheat (Triticum aestivum L.) (Gustafson et al, 2005;Hucl, 1996;Hucl and Matus-Cadiz, 2001;Matus-Cadiz et al, 2007), oilseed rape (B. napus) (Beckie et al, 2003;Damgaard and Kjellsson, 2005;Rieger et al, 2002;Weekes et al, 2005) and maize (Zea mays L.) (Goggi et al, 2006(Goggi et al, , 2007Gustafson et al, 2006;Weekes et al, 2007) (reviewed in Beckie andHall, 2008). Because of differences in research design and source plot size, studies are difficult to compare directly.…”
Section: Discussionmentioning
confidence: 99%
“…Pollen-mediated gene flow has been quantified in detail in several crops using transgenic and marker genes including wheat (Triticum aestivum L.) (Gustafson et al, 2005;Hucl, 1996;Hucl and Matus-Cadiz, 2001;Matus-Cadiz et al, 2007), oilseed rape (B. napus) (Beckie et al, 2003;Damgaard and Kjellsson, 2005;Rieger et al, 2002;Weekes et al, 2005) and maize (Zea mays L.) (Goggi et al, 2006(Goggi et al, , 2007Gustafson et al, 2006;Weekes et al, 2007) (reviewed in Beckie andHall, 2008). Because of differences in research design and source plot size, studies are difficult to compare directly.…”
Section: Discussionmentioning
confidence: 99%
“…Gustafson et al (2005) reported that the size of the pollen source had little effect on gene flow frequency in the field using a model of wheat gene flow frequency. Furthermore, no significant effect on gene flow frequency was detected from the test carried out by Rong (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were drawn by Hanson et al (2005b) and Gatford et al (2006). Using a Nelder wheel design with a central pollinator source (0.16 ha), Hanson et al (2005b) Based on data from previous studies, Gustafson et al (2005) developed an empirical model which demonstrated that even in the absence of buffer zones, gene flow in harvested-blended (harvested grain from entire field blended together) wheat would be B0.1%, well below any labeling thresholds. However, Willenborg and Van Acker (2006) contend that there are serious problems with both the approach taken and conclusions drawn from the model results.…”
Section: Intraspecific and Interspecific Gene Flowmentioning
confidence: 99%